Perfluoropolyether Nanoemulsion Encapsulating Chlorin e6 for Sonodynamic and Photodynamic Therapy of Hypoxic Tumor - Liang Hong; Artem M. Pliss; Ye Zhan; Wenhan Zheng; Jun Xia; Liwei Liu; Junle Qu; Paras N. Prasad (Nanomaterials, 2020)
Sonodynamic therapy (SDT) has emerged as an important modality for cancer treatment. SDT utilizes ultrasound excitation, which overcomes the limitations of light penetration in deep tumors, as encountered by photodynamic therapy (PDT) which uses optical excitations. A comparative study of these modalities using the same sensitizer drug can provide an assessment of their effects. However, the efficiency of SDT and PDT is low in a hypoxic tumor environment, which limits their applications. In this study, we report a hierarchical nanoformulation which contains a Food and Drug Administration (FDA) approved sensitizer chlorin, e6, and a uniquely stable high loading capacity oxygen carrier, perfluoropolyether. This oxygen carrier possesses no measurable cytotoxicity. It delivers oxygen to overcome hypoxia, and at the same time, boosts the efficiency of both SDT and PDT. Moreover, we comparatively analyzed the efficiency of SDT and PDT for tumor treatment throughout the depth of the tissue. Our study demonstrates that the strengths of PDT and SDT could be combined into a single multifunctional nanoplatform, which works well in the hypoxia environment and overcomes the limitations of each modality. The combination of deep tissue penetration by ultrasound and high spatial activation by light for selective treatment of single cells will significantly enhance the scope for therapeutic applications.